A Taxonomic revision of Pseudodissochaeta (Melastomataceae, Dissochaeteae) - Kartonegoro, Abdulrokhman; Liu, Ying; Mota De Oliveira, Sylvia; van Welzen, Peter (Phytotaxa, 2020)
The mainly Southeast Asian genus Pseudodissochaeta (Melastomataceae, Dissochaeteae) is revised based on a study of herbarium collections. The relationships of Pseudodissochaeta to Dissochaeta and Medinilla are discussed and some important characters distinguishing it from its relatives, including habit, leaf base and margin and floral characters, are provided. Five species are recognized without any infraspecific taxa. A key to the species, descriptions of each species, distribution (maps), ecology, habitat, images and a list of the specimens examined are given.